2022
DOI: 10.3390/ijms232314968
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive Effect of Natural Products and Their Derivatives Targeting BDNF-TrkB in Gut–Brain Axis

Abstract: Modern neurological approaches enable detailed studies on the pathophysiology and treatment of depression. An imbalance in the microbiota–gut–brain axis contributes to the pathogenesis of depression. This extensive review aimed to elucidate the antidepressive effects of brain-derived neurotrophic factor (BDNF)-targeting therapeutic natural products and their derivatives on the gut–brain axis. This information could facilitate the development of novel antidepressant drugs. BDNF is crucial for neuronal genesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…Therefore, AKT and MAPK signaling pathways were considered pathways of interest. Previous studies found that CUMS, CRS and LH models of depression reduced the AKT signaling pathway in the hippocampus of mice and that CUMS activated the MAPK signaling pathway [ 37 40 ]. Moreover, p-AKT and p-MEK1 were commonly altered in four depression models.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AKT and MAPK signaling pathways were considered pathways of interest. Previous studies found that CUMS, CRS and LH models of depression reduced the AKT signaling pathway in the hippocampus of mice and that CUMS activated the MAPK signaling pathway [ 37 40 ]. Moreover, p-AKT and p-MEK1 were commonly altered in four depression models.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants and their bioactive constituents offer substantial health-promoting advantages, thereby warranting their utilization for the management of various ailments such as cancer, gastrointestinal disorders, and hepatic injury ( Cheema and Singh, 2021 ; Khosravifarsani et al, 2022 ; Parganiha et al, 2022 ). Plant-derived polysaccharides represent crucial active components possessing anti-inflammatory, antioxidant, and immunomodulatory properties ( Farahani et al, 2015 ; Wang et al, 2022a ; Liaqat et al, 2022b ), with notable evidence supporting their potential antidepressant effects.…”
Section: Antidepressant Mechanism Of Natural Plant Polysaccharidesmentioning
confidence: 99%
“…Plant-derived polysaccharides represent crucial active components possessing anti-inflammatory, antioxidant, and immunomodulatory properties (Farahani et al, 2015;Wang et al, 2022a;Liaqat et al, 2022b), with notable evidence supporting their potential antidepressant effects.…”
Section: Polysaccharides Regulate the Oxidative Stressmentioning
confidence: 99%
“…Additionally, as previously mentioned, iron overload may contribute to depression by downregulating the expression of BDNF ( LI J. et al, 2023 ; SHKUNDIN and HALARIS, 2023 ). Recent research has demonstrated that alterations in gut microbiota distribution, according to the brain-gut axis mechanism, can modulate BDNF expression, thereby influencing the onset of depression ( LIAQAT et al, 2022 ). Moreover, a meta-analysis revealed decreased levels of Corprococcus and Faecalibacterium bacteria in the intestines of individuals with depression compared to healthy individuals.…”
Section: Depression and Ferroptosismentioning
confidence: 99%
“…Towards the end of the 20th century, a close association between increased TfR1 expression and depression was identified in patients with this condition (MAES et al, 1995a). This suggests that individuals with depression may exhibit a higher propensity for the excessive accumulation of iron ions, resulting in neuronal ferroptosis (MAES et al, 1995b;LIANG et al, 2020). However, some researchers further demonstrated, through a cross-sectional study, that ferroptosis is not related to the severity of depression (ZHANG et al, 2019).…”
Section: Iron Deposition In Depressionmentioning
confidence: 99%